Efecto de la agricultura regenerativa para disminuir las emisiones de carbono en el ambiente. - Muñoz Iglesias, Bryan Ronny (2023)
Academic research examines the complex relationship between terrestrial ecosystems and increasing atmospheric carbon dioxide (CO2) emissions. It focuses on how industrialization, agriculture and the use of synthetic chemicals have raised CO2 rates, depleting soil carbon stocks through intensive agricultural practices. Regenerative agriculture emerges as a key solution, focusing on carbon sequestration and improving soil health. The research, based on a comprehensive literature review, highlights the importance of organic carbon in soil for stability and resistance to extreme weather events. It highlights the essential role of agricultural practices, such as crop rotation and the use of waste to produce biomass, in mitigating climate change and adapting to changing conditions. In addition, the potential of composting is explored, noting that, when used as an organic amendment in agriculture, CO2 released during the process is part of the natural carbon cycle, not contributing to the net increase of CO2 in the atmosphere. It stresses the resilience that crop diversification gives farmers in the face of extreme weather events. Finally, the growing role of regenerative agriculture in global sustainability is emphasized. It is concluded that this practice can not only mitigate climate change and improve soil health, but also boost the adaptation and resilience of agricultural communities to climate challenges, offering a hopeful path to a more sustainable and equitable future.